Proceso logístico de industrias lácteas Toni S.A. sucursal Babahoyo - Onofre Bravo, Luis Angel (2021)
La Industria lactea Toni SA is currently located in Babahoyo - kilometer 3 ½ via Juan, this company is dedicated to the manufacture and distribution of dairy products, this study of chaos aims to know how the company's logistics process is being carried out , since through the investigation it has been possible to obtain that there are several shortcomings in the department in which it has caused low profitability both in productivity and in sales. On the other hand, through the results, it was possible to know that logistics is not handled efficiently, since at the time of shipment, the necessary measures are not taken so that the requirements of the clients are fully met. does the dispatch, they complain because the full order is not delivered and they even tend to arrive damaged, in addition to not having a refrigerator that keeps the yogurt in good condition causes the product to be damaged since when it perishes from this, the merchandise registers weekly damage generating a loss for the company, in times of pandemic products were registered close to expiration, at the time of delivery there were rejections since their expiration date was very early, there were delays when making changes